Efficacy of Ophthalmic Viscosurgical Devices in Preventing Temperature Rise at the Corneal Endothelium during Phacoemulsification. (1st December 2016) - Suzuki, Hisaharu; Igarashi, Tsutomu; Shiwa, Toshihiko; Takahashi, Hiroshi
ABSTRACT: Purpose : To investigate temperature alterations in the aqueous humor and the corneal endothelium during phacoemulsification, and to evaluate the effect of ophthalmic viscosurgical devices in preventing a temperature rise at the corneal endothelium during phacoemulsification. Methods : Temperatures of the aqueous humor and corneal endothelium were measured using two temperature probes set in the anterior chamber during ultrasound oscillation in porcine eyes, with or without ophthalmic viscosurgical devices. Results : Without an ophthalmic viscosurgical device, temperatures in both the aqueous humor and the corneal endothelium rapidly rose during the ultrasound oscillation, while with an ophthalmic viscosurgical device, the temperature elevation of the corneal endothelium site was suppressed compared with the aqueous humor. Conclusion : Surgeons need to be especially aware of ophthalmic viscosurgical device retention during phacoemulsification, because it can protect the corneal endothelium from heat generated during this procedure.